The Effect Of Location, Availability Of Products And Prices On Purchase Decisions At Nipis Tani Shop Bengkulu Selatan - Aprian; Ida Anggriani; Ida Ayu Made Er Meytha Gayatri (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2021)
The purpose of this study was to determine the effect of location, product availability and price on purchasing decisions at Air Nipis Tani Shop, South Bengkulu Regency. The population and sample in this research are 75 people. The sampling technique uses accidental sampling, which is a sampling technique carried out with respondents who happen to be present or available. The data is processed in the form of numerical data (numbers) using a Likert scale. Data collection methods in this study were questionnaires and literature study. Data is processed using SPSS for Windows version 20.0. Methods of data analysis using quantitative methods, namely by using multiple linear regression analysis. The results of the study with multiple linear regression analysis (Y = a + β₁X₁ + β₂X₂ + β3X3 + e) ​​prove that the variables of location, product availability and price have a significant influence on purchasing decision variables at the Nipis Tani Air Store, South Bengkulu Regency. The biggest significant influence on purchasing decisions at the Nipis Tani Water Store is the location variable with a standard beta coefficient of 5.213 followed by the product availability variable with a beta coefficient of 4.645, then the beta coefficient price variable of 3.055, then location, product availability and price with a value The significance of Fcount is 30.753. From the results of this analysis, it can be concluded that location is the dominant factor that has the greatest influence on the tendency of purchasing decisions at the Air Nipis Tani Shop, South Bengkulu Regency.